Implikasi Hukum Terkait Dengan Pelaksanaan Pasal 24 Undang-Undang Nomor 41 Tahun 2004 Tentang Wakaf - Sabri Fataruba (SASI, 2018)
Article 24 of Law Number 41 Year 2004 on Wakaf states that wakaf with testament both orally and in writing can only be done if witnessed by at least 2 (two) witnesses who meet the requirements. The statement that wakaf with a will, either orally or in writing can only be done if witnessed by at least 2 (two) witnesses fulfilling the requirements as meant in Article 24 of Law Number 41 Year 2004 above means that if the endowers with oral or written testimony is not witnessed by at least 2 (two) witnesses who fulfill the requirements, it will have a legal effect on the validity of the waqf status. However, after the following articles and / or paragraphs of Law Number 41 Year 2004 along with their explanation, as well as Government Regulation Number 42 of 2006 on Implementation of Law Number 41 Year 2004 About Wakaf, Â there was notÂ  found any article explains what legal implications would be if the wakaf testament is not witnessed by at least 2 (two) witnesses who meet the requirements. Therefore, in order to overcome the incompleteness resulting in the ineffectiveness of Article 24, if there are any concrete events related to the will of judgment submitted to the court to be resolved, the judge shall be able to use the method of legal discovery, either according to the science of law or according to Islamic law appropriately, so it can provide legal certainty for justice seekers.